Wildflowers and Wonder: A Pastor's Wanderings in the Religion-Science Wilderness - Jones, Linda Jarchow (Zygon, 1994)
Abstract. In this paper, I explore, as a Christian and a parish pastor, what drew me into the religion-science dialogue and what keeps me involved. Encounters with nature and readings of evolutionary theory answer some questions and raise others, especially questions about chance and the nature of God. I persist in my quest for understanding because creedal affirmations of God as Creator demand an examination of the relationship between God and the world, and because I want to proclaim the Christian message in a credible way to parishioners raised with a scientific worldview. Along the way I am reaping unexpected spiritual dividends.